2018
DOI: 10.1080/00913367.2018.1463880
|View full text |Cite
|
Sign up to set email alerts
|

Active White Space (AWS) in Logo Designs: Effects on Logo Evaluations and Brand Communication

Abstract: In this paper, we explore Active White Space (AWS) (space between individual logo design elements) as a stylistic modification that revamps a logo design, yet preserves its extant associations. Across three studies, we find AWS to be an effective stylistic logo tool. In Study 1, we find that adding AWS to pictorial logos improves their visual evaluation. In Study 2, we find this positive evaluation to spill-over to verbal brand aspects such that logo designs with AWS are perceived to communicate brand descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Fourth, the middle-width spacing of the motifs was the most preferred among the three stimulus examples, followed by the widest space. Our results support the assertion that blank spaces allow for a sense of relaxation and are felt as luxuriousness or sophistication [ 42 ].…”
Section: Discussionsupporting
confidence: 88%
“…Fourth, the middle-width spacing of the motifs was the most preferred among the three stimulus examples, followed by the widest space. Our results support the assertion that blank spaces allow for a sense of relaxation and are felt as luxuriousness or sophistication [ 42 ].…”
Section: Discussionsupporting
confidence: 88%
“…Fifth, the current findings enhance the understanding and use of frames or boundaries in marketing beyond just consumption contexts and logo designs (Cutright, 2012; Fajardo et al , 2016; Sharma and Varki, 2018). Finally, our work also extends prior marketing research on product effectiveness (Chae et al , 2013; Ilyuk and Block, 2016).…”
Section: Theoretical Implicationsmentioning
confidence: 76%
“…Moving the same ad from a quarter-page to a full-page layout (thereby increasing the amount of white space) increases consumer tendency to categorize the brand as a market leader (Pracejus et al , 2006). More recently, Sharma and Varki (2018) show that adding white space between individual logo design elements improves the logo’s visual evaluations as well as the perceived clarity of its intended brand communication. In this paper, we follow Pracejus et al ’s (2006, p. 82) definition of white space as “the conspicuously open space found between design elements or objects within the borders of an ad”.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding white space to a logo increased design cleanliness and visual balance (Pracejus et al, 2006), which improved the perceptual fluency due to the ease of visual processing among design features. Sharma and Varki (2018) showed that perceptual fluency could spill over to consumers' attitudes toward a brand. Thus, the halo or spillover effect by removing logo frames and adding white space to a logo design (i.e.…”
Section: Theoretical Background Of Study 2 Perceived Fit Of New Brandmentioning
confidence: 99%